A Study on the Bharat Ratna Dr.Maruthur Gopala Menon Ramachandran Film Songs that Contain the Ideas of Equity and Social Justice a A Comparative Analysis with the Contemporary Theories more Specifically with the Theory of Socialism as Propounded by Karl Marx. (Global Journal of Human-Social Science, 2018)
It is a fact that super-hero like Makkal Thilagam Bharat Ratna Dr. M.G. Ramachandran took upon himself the responsibility of not only producing quality movies but
Keywords: bharat ratna drmgramachandran; karl marx; context; equity and social justice; communist manifesto; alienation; thatai periyar; peraringer anna; pur